Polyacid-based inorganic-organic hybrid compound, preparation method thereof and application of polyacid-based inorganic-organic hybrid compound in photocatalytic degradation of antibiotics
By using the polyacid-based inorganic-organic hybrid compound [Cu2Mo2O8 (C10N2H8)] as a catalyst, using its three-dimensional network cavity structure and semiconductor-like structure, the problems of catalyst pollution and low efficiency during photocatalytic degradation of antibiotics in the prior art were solved, and an efficient and environmentally friendly antibiotic removal effect was achieved.
Patent Information
- Application Number
- CN202510063844.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In the photocatalytic degradation of antibiotics, the prior art has problems such as water pollution threat of cadmium ions in the catalyst, long catalytic time and low efficiency, incomplete degradation, high cost and difficult to recover.
The polyacid-based inorganic-organic hybrid compound [Cu2Mo2O8 (C10N2H8)] is used as a catalyst. This compound has a three-dimensional network cavity structure and a semiconductor-like structure. By introducing a transition metal to adjust the band gap width of the material, the separation efficiency of photogenerated electrons/holes is improved.
Efficient photocatalytic degradation of antibiotics is achieved, the removal rate of antibiotics is improved, the threat of cadmium ions is avoided, and the cost is reduced.
Smart Images

Figure CN119874782A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of functional crystalline materials, and in particular relates to a polyacid-based inorganic-organic hybrid compound, a preparation method thereof and application thereof in photocatalytic degradation of antibiotics. Background Art
[0002] Antibiotics are hailed as one of the major achievements in the history of microbiology due to their excellent therapeutic effects on bacterial infections. Among them, quinolone antibiotics are currently the most widely used antibiotics in clinical practice. Excessive and improper use of quinolone antibiotics has led to the residues of quinolone antibiotics in animal foods, increased drug resistance, ecological effects in the environment, and harm to human health through the food chain, which has attracted widespread attention. Therefore, seeking a reasonable method to degrade antibiotics is crucial to protecting human health and environmental safety. Traditional methods for treating quinolone antibiotics are filtration, biodegradation, and reverse osmosis, but these methods are limited due to their high cost or incomplete treatment. Patent (CN202311805915.5) discloses a quinolone antibiotic degrading bacterium, a bacterial agent, and its preparation method and application. Achromobacter has excellent degradation effects on quinolone antibiotics such as levofloxacin, moxifloxacin, and enoxacin. Under a concentration of 100-500 mg / L, the 48h degradation rate can reach more than 95%, but the culture process of Achromobacter is complicated and the cost is high. Solar energy is a clean renewable energy source that can fundamentally solve the problems of environmental pollution and energy shortage. Photocatalytic degradation of organic pollutants has the advantages of fast speed, no secondary pollution, and energy saving. The core of photocatalytic technology lies in the design of catalysts with excellent performance and stable structure. At present, the catalyst is mainly a composite material. The patent (CN 113398955 B) discloses a preparation method of Sillén-type bimetallic halide oxide for antibiotic degradation. The invention uses 1-hexadecyl-3-methylimidazole bromide as a bromine source and cadmium acetate dihydrate as a cadmium source. The product is synthesized by solvothermal method in a mixed solution of water and mannitol. The product is cooled, filtered and washed, and air-dried to obtain CdBiO 2 Br ultra-thin nanosheets were used for photocatalytic degradation of ciprofloxacin. After 210 minutes of visible light irradiation, the degradation rate of ciprofloxacin was 79.44%. However, the main catalytic site cadmium ions in the catalyst pose a threat to water pollution and human health, and the catalytic time is long and the efficiency is low. The existing antibiotic removal technology also has the disadvantages of incomplete degradation, high cost, and difficulty in recycling. Summary of the invention
[0003] The purpose of the present invention is to at least partially solve the above-mentioned technical problems, and aims to provide a polyacid-based inorganic-organic hybrid compound, a preparation method thereof and its application in photocatalytic degradation of antibiotics. The synthesized polyacid-based inorganic-organic hybrid compound has a three-dimensional cavity structure and excellent photocatalytic degradation performance of antibiotics.
[0004] In a first aspect of the present invention, there is provided a polyacid-based inorganic-organic hybrid compound, wherein the chemical formula of the polyacid-based inorganic-organic hybrid compound is [Cu 2 Mo 2 O 8 (C 10 N 2 H 8 )], the crystallographic parameters are:
[0005] In some embodiments of the present invention, the polyacid-based inorganic-organic hybrid compound has a three-dimensional network cavity structure.
[0006] The second aspect of the present invention provides a method for preparing the above-mentioned polyacid-based inorganic-organic hybrid compound, the preparation method comprising the following steps:
[0007] S1. Na 2 MoO 4 ·2H 2 O was dissolved in water, and concentrated H 3 PO 4 and concentrated HCl, stirred, then added ether, shaken until completely mixed, cooled and allowed to stand until the solution separated into layers, the lower layer of solution was taken, extracted and purified to obtain H 3 [PMo 12 O 40 ];
[0008] S2. H 3 [PMo 12 O 40 ], 4,4'-bipy and Cu(NO 3 ) 2 After mixing, add H 2 O and DMF, stir evenly, heat to react, and cool to room temperature to obtain the polyacid-based inorganic-organic hybrid compound.
[0009] In some embodiments of the present invention, the extraction purification is to remove H 3 [PMo 12 O 40 ] mixed with Na 2 MoO 4 ·2H 2 O, H 3 PO4 and HCl, the specific steps are:
[0010] Add water to the lower solution, then add ether, shake until mixed, let stand until the solution separates, and take the lower solution;
[0011] Add water to the lower solution and slowly drop concentrated HNO 3 When the solution turns yellow, heat the reaction to obtain pure product H 3 [PMo 12 O 40 ];
[0012] In some embodiments of the present invention, in step S2 of the above preparation method, H 3 [PMo 12 O 40 ], 4,4'-bipy and Cu(NO 3 ) 2 The mass ratio is (0.01-0.05):(0.001-0.015):(0.001-0.05).
[0013] In some embodiments of the present invention, in step S2 of the above preparation method, the heating reaction is specifically: reacting at 100-150° C. for 24-56 hours.
[0014] In some embodiments of the present invention, in step S2 of the above preparation method, H 3 [PMo 12 O 40 ]、H 2 The usage ratio of O and DMF is (0.01-0.05) g:5 mL:1 mL.
[0015] The third aspect of the present invention provides a use of the above-mentioned polyacid-based inorganic-organic hybrid compound or the polyacid-based inorganic-organic hybrid compound prepared by the above-mentioned preparation method as a catalyst in the photocatalytic degradation of antibiotics.
[0016] In some embodiments of the present invention, the photocatalytic degradation of antibiotics is visible light catalytic degradation of antibiotics.
[0017] The fourth aspect of the present invention provides a method for photocatalytic degradation of antibiotics, the method comprising: adding a catalyst to a solution containing the antibiotics, stirring until adsorption-desorption equilibrium is reached, and then performing a photoreaction under visible light irradiation, wherein the catalyst is the above-mentioned polyacid-based inorganic-organic hybrid compound or the polyacid-based inorganic-organic hybrid compound prepared by the above-mentioned preparation method.
[0018] In some embodiments of the present invention, the dosage ratio of the catalyst to the solution containing antibiotics is 15 mg:50 mL, and the concentration of antibiotics in the solution containing antibiotics is (10-20) mg / L.
[0019] The polyacid-based inorganic-organic hybrid compound, the preparation method thereof and the application thereof in photocatalytic degradation of antibiotics according to the embodiments of the present invention have at least one of the following advantages:
[0020] (1) The polyacid-based inorganic-organic hybrid compound provided by the present invention has a three-dimensional network cavity structure, and the cavity structure contributes to high adsorption of antibiotics;
[0021] (2) The band gap width of the polyacid-based inorganic-organic hybrid compound provided by the present invention is adjusted by introducing a transition metal to form a semiconductor-like structure, which is beneficial to improving the separation efficiency of photogenerated electrons / holes, enhancing the photocatalytic efficiency under visible light, and improving the removal rate of antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of preferred embodiments in conjunction with the accompanying drawings, in which:
[0023] Figure 1 A 3D structural diagram of the polyacid-based inorganic-organic hybrid compound provided by the present invention;
[0024] Figure 2 A chemical structure diagram of the polyacid-based inorganic-organic hybrid compound provided by the present invention;
[0025] Figure 3 This is an infrared spectrum of the polyacid-based inorganic-organic hybrid compound prepared in Example 1 of the present invention;
[0026] Figure 4 This is a diagram of the photocatalytic degradation of the polyacid-based inorganic-organic hybrid compound in Test Example 2. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.
[0028] The raw materials used in the following examples are all commercially available products, among which concentrated H 3 PO 4 The concentration was 85 wt % and the concentration of concentrated HCl was 37 wt %.
[0029] Example 1
[0030] 1. Weigh 10.5g Na 2 MoO 4 ·2H 2 O and dissolve in 21 mL of distilled water, stir until completely dissolved, and add 1 mL of concentrated H 3 PO 4 , then add 10 mL of concentrated HCl and stir for 40 min.
[0031] 2. Transfer the solution to a 250mL separatory funnel, take 15mL of ether and shake manually for 30min until the solution is completely mixed. Cool and let stand for 20min. Separate the solution into layers and take out the lower layer.
[0032] 3. Add 10 mL of distilled water to the lower layer solution obtained in step 2, shake for 3 min, then add 8 mL of ether, shake for 30 min, let stand, separate the solution into layers, and separate the lower layer.
[0033] 4. Add 2 mL of distilled water to the lower solution obtained in step 3. The solution will turn blue. Slowly add concentrated HNO 3 , until it turns yellow, and then place in a water bath at 80°C for 30 min. A large amount of yellow solid is produced. Separate and dry to obtain pure product H 3 [PMo 12 O 40 ].
[0034] 5. Weigh 0.024g H 3 [PMo 12 O 40 ], 0.009g4,4'-bipy, 0.011gCu(NO 3 ) 2 Put it into a polytetrafluoroethylene bottle and add 5mL of H 2 O and 1 mL DMF. After stirring for 30 min, the mixture was placed in a hydrothermal synthesis reactor and placed in an oven at 120 °C for 48 h. After cooling to room temperature, the product was obtained as grass green crystals.
[0035] Example 2
[0036] 1. Weigh 10.5g Na 2 MoO 4 ·2H 2 O and dissolve in 21 mL of distilled water, stir until completely dissolved, and add 1 mL of concentrated H 3 PO 4 , then add 10 mL of concentrated HCl and stir for 40 min.
[0037] 2. Transfer the solution to a 250mL separatory funnel, take 15mL of ether and shake manually for 30min until the solution is completely mixed. Cool and let stand for 20min. Separate the solution into layers and take out the lower layer.
[0038] 3. Add 10 mL of distilled water to the lower layer solution obtained in step 2, shake for 3 min, then add 8 mL of ether, shake for 30 min, let stand, separate the solution into layers, and separate the lower layer.
[0039] 4. Add 2 mL of distilled water to the lower solution obtained in step 3. The solution turns blue. Slowly add concentrated HNO 3 , until it turns yellow, and then add water at 80℃ for 30min, a large amount of yellow solid is produced, which is separated and dried to obtain product H 3 [PMo 12 O 40 ].
[0040] 5. Weigh 0.024g H 3 [PMo 12 O 40 ], 0.018g4,4'-bipy, 0.011gCu(NO 3 ) 2 Put it into a polytetrafluoroethylene bottle and add 5mL of H 2 O and 1 mL DMF. After stirring for 30 min, the mixture was placed in a hydrothermal synthesis reactor and placed in an oven at 120 °C for 48 h. After cooling to room temperature, the product was obtained as grass green crystals.
[0041] Example 3
[0042] 1. Weigh 10.5g Na 2 MoO 4 ·2H 2 O and dissolve in 21 mL of distilled water, stir until completely dissolved, and add 1 mL of concentrated H 3 PO 4 , then add 10 mL of concentrated HCl and stir for 40 min.
[0043] 2. Transfer the solution to a 250mL separatory funnel, take 15mL of ether and shake manually for 30min until the solution is completely mixed. Cool and let stand for 20min. Separate the solution into layers and take out the lower layer.
[0044] 3. Add 10 mL of distilled water to the lower layer solution obtained in step 2, shake for 3 min, then add 8 mL of ether, shake for 30 min, let stand, separate the solution into layers, and separate the lower layer.
[0045] 4. Add 2 mL of distilled water to the lower solution obtained in step 3. The solution will turn blue. Slowly add concentrated HNO 3, until it turns yellow, and then add water at 80℃ for 30min, a large amount of yellow solid is produced, which is separated and dried to obtain product H 3 [PMo 12 O 40 ].
[0046] 5. Weigh 0.048g H 3 [PMo 12 O 40 ], 0.018g4,4'-bipy, 0.011gCu(NO 3 ) 2 Put it into a polytetrafluoroethylene bottle and add 5mL of H 2 O and 1 mL DMF. After stirring for 30 min, the mixture was placed in a hydrothermal synthesis reactor and placed in an oven at 120 °C for 48 h. After cooling to room temperature, the product was obtained as grass green crystals.
[0047] Test Example 1
[0048] A single crystal of the polyacid-based inorganic-organic hybrid compound (denoted as Compound 1) with a size of 10*12*15 mm prepared in Example 1 was selected and mounted on a glass fiber or sealed in a glass tube, and then directly transferred to a 293(2)K graphite monochromator equipped with MoKα The structure was solved by direct method and refined by full matrix least square method using SHELX 97 program package. The crystals obtained in Examples 2 and 3 were subjected to unit cell test, and the results were consistent with the crystal unit cell obtained in Example 1, indicating that they were the same structure.
[0049] The detailed crystallographic data of the compound are shown in Table 1. The crystal structure is shown in Figure 1 and 2 The structure of the compound was further confirmed by infrared spectroscopy ( Figure 3 ) was characterized, 1000~500cm -1 The absorption peaks in the range are mainly the characteristic absorption peaks of the polyacid skeleton, 935, 887, 817, 791, 734 and 648 cm -1 The peaks at 3300-1000cm -1 The absorption peaks in the range of 3099, 3053, 3016, 2362, 1614, 1535, 1494, 1413, 1224 and 1076 cm -1 The characteristic absorption peak at 3464cm -1 There is a broad and weak absorption band, which is the absorption band of crystal water.
[0050] Table 1 Crystallographic parameters of compounds
[0051]
[0052]
[0053] Test Example 2
[0054] Using ofloxacin as the substrate antibiotic, the synthesized compounds 1, H 3 [PMo 12 O 40 ]、4,4'-bipy、Cu(NO 3 ) 2 The degradation experiment was carried out in a 100 mL quartz photoreactor. The circulating water device was turned on to keep the system temperature at 25 ± 0.5 °C and the speed was adjusted. The light source was a 300 W xenon lamp. 15 mg of the photocatalyst (sample 1) was added to 50 mL of a 10 mg·L -1 ofloxacin solution. After stirring in the dark for 30 min to reach adsorption-desorption equilibrium, the photoreaction was carried out under light irradiation. 3 mL of the suspension was extracted every 30 min, centrifuged and filtered with a 0.22 μm filter to remove catalyst particles. The concentration of the antibiotic after degradation was determined by high performance liquid chromatography ( Figure 4 ). A C18 column was used. The wavelength of the UV-vis detector was set to 288 nm, the mobile phase was methanol (A) and 1‰ formic acid aqueous solution (B), the volume ratio was 15:85, and the flow rate was 1.0 mL min -1 The injection volume was 10 μL. The comparison results showed that the compound 1 provided by the present invention has excellent photocatalytic degradation activity of ofloxacin antibiotics
[0055] The polyacid-based inorganic-organic hybrid compound, the preparation method thereof and the application thereof in photocatalytic degradation of antibiotics according to the embodiments of the present invention have at least one of the following advantages:
[0056] The polyacid-based inorganic-organic hybrid compound, the preparation method thereof and the application thereof in photocatalytic degradation of antibiotics according to the embodiments of the present invention have at least one of the following advantages:
[0057] (1) The polyacid-based inorganic-organic hybrid compound provided by the present invention has a three-dimensional network cavity structure, and the cavity structure contributes to high adsorption of antibiotics.
[0058] (2) The band gap width of the polyacid-based inorganic-organic hybrid compound provided by the present invention is adjusted by introducing a transition metal to form a semiconductor-like structure, which is beneficial to improving the separation efficiency of photogenerated electrons / holes, enhancing the photocatalytic efficiency under visible light, and improving the removal rate of antibiotics.
Claims
1. A polyacid-based inorganic-organic hybrid compound, characterized in that: The chemical formula of the polyacid-based inorganic-organic hybrid compound is [Cu2Mo2O8(C 10 N2H8)], the crystallographic parameters are:
2. The polyacid-based inorganic-organic hybrid compound according to claim 1, characterized in that: The polyacid-based inorganic-organic hybrid compound has a three-dimensional network cavity structure.
3. A method for preparing the polyacid-based inorganic-organic hybrid compound according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Dissolve Na2MoO4·2H2O in water, add concentrated H3PO4 and concentrated HCl in turn, stir, then add ether, shake until completely mixed, cool and stand until the solution separates, take the lower layer of solution, extract and purify, and obtain H3[PMo 12 O 40 ]; S2. H3[PMo 12 O 40 ], 4,4'-bipy and Cu(NO3)2 are mixed, H2O and DMF are added, stirred evenly, heated for reaction, and cooled to room temperature to obtain the polyacid-based inorganic-organic hybrid compound.
4. The preparation method according to claim 3, characterized in that: In step S2, H3[PMo 12 O 40 ], 4,4'-bipy and Cu(NO3)2 have a mass ratio of (0.01-0.05):(0.001-0.015):(0.001-0.05).
5. The preparation method according to claim 3, characterized in that: In step S2, the heating reaction is specifically: reacting at 100-150°C for 24-56 hours.
6. The preparation method according to claim 4, characterized in that: In step S2, H3[PMo 12 O 40 ], the dosage ratio of H2O and DMF is (0.01-0.05) g:5 mL:1 mL.
7. Use of the polyacid-based inorganic-organic hybrid compound according to claim 1 or 2 or the polyacid-based inorganic-organic hybrid compound prepared by the preparation method according to any one of claims 2 to 6 as a catalyst in photocatalytic degradation of antibiotics.
8. The use according to claim 7, characterized in that: The photocatalytic degradation of antibiotics is the photocatalytic degradation of antibiotics by visible light.
9. A method for photocatalytic degradation of antibiotics, characterized in that: The method comprises: adding a catalyst to a solution containing an antibiotic, stirring until adsorption-desorption equilibrium is reached, and then performing a photoreaction under visible light irradiation, wherein the catalyst is the polyacid-based inorganic-organic hybrid compound according to claim 1 or 2 or the polyacid-based inorganic-organic hybrid compound prepared by the preparation method according to any one of claims 2 to 6.
10. The method according to claim 9, characterized in that The dosage ratio of the catalyst to the solution containing antibiotics is 15 mg:50 mL, and the concentration of antibiotics in the solution containing antibiotics is (10-20) mg / L.
Citation Information
Patent Citations
POM (polyoxometalate)-based crystal material adopting 3D intercalation structure and preparation method of POM-based crystal material
CN109092365A
Organic silicon dioxide loaded PMoW polyacid photocatalytic material as well as preparation method and application thereof
CN113842933A
Polyacid-based metal organic framework material as well as preparation method and application thereof
CN115490877A
Preparation method and application of Keggin type transition metal heteropolyacid salt modified photocatalyst
CN116532159A
Preparation method and application of heterojunction photocatalytic material for degrading fluoroquinolone antibiotics
CN117414874A